2007
DOI: 10.2193/2006-263
|View full text |Cite
|
Sign up to set email alerts
|

Woodland Caribou Extirpation and Anthropogenic Landscape Disturbance in Ontario

Abstract: The decline of woodland caribou (Rangifer tarandus caribou) has been attributed to anthropogenic landscape disturbances, but critical distance thresholds and time lags between disturbance and extirpation are unknown. Using a database of caribou presence and extirpation for northern Ontario, Canada, geo‐coded to 10 times 10‐km cells, we constructed logistic regression models to predict caribou extirpation based on distance to the nearest of each of 9 disturbance types: forest cutovers, fires, roads, utility cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
143
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(157 citation statements)
references
References 44 publications
(53 reference statements)
13
143
0
1
Order By: Relevance
“…Additional benefits provided through the collection of faecal pellets include the potential for other genetics based testing in assessing population bottlenecks (Petersen et al, 2010), metapopulation structure and sex-ratios (Vors, 2006) and other faecal-based parameters, including: hormonal information to assess pregnancy and stress indicators (Messier et al, 1990;Vors, 2006), the size of pellets as an indicator of age-range (Ball, 2010), diet information (Boertje, 1990) and parasite load (Gray & Samuel, 1986). In conducting multiyear sampling events there is also the potential for the use of open population models where population demographic parameters including population rate of growth and recruitment rates can be estimated (Hettinga, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Additional benefits provided through the collection of faecal pellets include the potential for other genetics based testing in assessing population bottlenecks (Petersen et al, 2010), metapopulation structure and sex-ratios (Vors, 2006) and other faecal-based parameters, including: hormonal information to assess pregnancy and stress indicators (Messier et al, 1990;Vors, 2006), the size of pellets as an indicator of age-range (Ball, 2010), diet information (Boertje, 1990) and parasite load (Gray & Samuel, 1986). In conducting multiyear sampling events there is also the potential for the use of open population models where population demographic parameters including population rate of growth and recruitment rates can be estimated (Hettinga, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this casestudy exemplifies the fragile equilibrium between habitat, predators, and caribou. Caribou is a highlyadaptable species that may persist for a long time in adverse environments (Vors et al, 2007); however, long time periods (> 40 years) are required for harvested stands to become unattractive to wolves and bears, and to become a suitable lichen-rich caribou habitat again. Telemetry flights recently revealed that many adult caribou in Charlevoix have died during the last few years, most of them from wolf predation.…”
Section: Uncertain Futurementioning
confidence: 99%
“…Numerous local populations have been extirpated, essentially because of overhunting and poaching, but also due to anthropogenic habitat modifications such as forest harvesting and road networks-both of which locally favour large predator populations (Schaefer, 2003;Racey & Arsenault, 2007;Vors et al, 2007). Now recognized as a threatened species by COSEWIC, woodland caribou receive much political attention and are considered of high conservation value (Mallory & Hillis, 1998;Environment Canada, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Vors et al (2007) concluded that a surrounding zone of intact forest of at least 13 km is needed to maintain woodland caribou in Ontario's northern boreal forest. The analysis has significant implications for woodland caribou management as it "contrasts starkly with current prescriptions for forest harvesting" (Vors et al, 2007(Vors et al, :1253.…”
Section: Policy Contextmentioning
confidence: 99%
“…However, there is consensus that even the largest protected areas in Ontario in which woodland caribou are present -Woodland Caribou Provincial Park (4500 km 2 ) and Wabakimi Provincial Park (8920 km 2 ) -are insufficient in of themselves for maintaining this species at risk (see Vors, 2006;Vors et al, 2007;Weirsma & Nudds, 2006). Woodland caribou require ranges in the order of thousands of square kilometres of little disturbed or undisturbed boreal forest (Rettie & Messier, 2001;Brown et al, 2003).…”
Section: The Role Of Protected Areasmentioning
confidence: 99%